A common polar dye additive as corrosion inhibitor and leveling agent for stable aqueous zinc‐ion batteries - Hao Wang; Chao Hu; Zefang Yang; Tingqing Wu; Yihu Li; Qi Zhang; Yougen Tang; Haiyan Wang (Electron)
Abstract The industrial application of zinc‐ion batteries is restricted by irrepressible dendrite growth and side reactions that resulted from the surface heterogeneity of the commercial zinc electrode and the thermodynamic spontaneous corrosion in a weakly acidic aqueous electrolyte. Herein, a common polar dye, Procion Red MX‐5b, with high polarity and asymmetric charge distribution is introduced into the zinc sulfate electrolyte, which can not only reconstruct the solvation configuration of Zn2+ and strengthen hydrogen bonding to reduce the reactivity of free H2O but also homogenize interfacial electric field by its preferentially absorption on the zinc surface. The symmetric cell can cycle with a lower voltage hysteresis (78.4 mV) for 1120 times at 5 mA cm−2 and Zn//NaV3O8·1.5H2O full cell can be cycled over 1000 times with high capacity (average 170 mAh g−1) at 4 A g−1 in the compound electrolyte. This study provides a new perspective for additive engineering strategies of aqueous zinc‐ion batteries.